2017
DOI: 10.1080/00958964.2017.1310083
|View full text |Cite
|
Sign up to set email alerts
|

The effect of gender on students' sustainability consciousness: A nationwide Swedish study

Abstract: Access to the published version may require subscription. N.B. When citing this work, cite the original published paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
42
3
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 38 publications
10
42
3
7
Order By: Relevance
“…It may be assumed that the program influenced some of the students, but not the majority. The issue of gender differences, i.e., educational programs' higher impact on girls compared with boys also has been found in other studies [51][52][53][54]; similar patterns were revealed in studies comparing the level of sustainability consciousness between boys and girls [55], while Goldman, Pe'er, and Yavetz [56] found these differences to be more complex. It could be assumed that the findings were affected by the low number of respondents in the control group, which has definitely been one of the limitations of the study.…”
Section: Discussionsupporting
confidence: 72%
“…It may be assumed that the program influenced some of the students, but not the majority. The issue of gender differences, i.e., educational programs' higher impact on girls compared with boys also has been found in other studies [51][52][53][54]; similar patterns were revealed in studies comparing the level of sustainability consciousness between boys and girls [55], while Goldman, Pe'er, and Yavetz [56] found these differences to be more complex. It could be assumed that the findings were affected by the low number of respondents in the control group, which has definitely been one of the limitations of the study.…”
Section: Discussionsupporting
confidence: 72%
“…A long (SCQ‐L) and short (SCQ‐S) version of the instrument have been developed. The reason for this is that when evaluating the effect of the implementation efforts of education for SD in the Swedish school system (Berglund et al, ; Boeve‐de Pauw et al, ; Olsson et al, ; Olsson & Gericke, , ) with the instrument, access to respondents was one of the main hurdles to overcome, due to shortage of time. This is also found to be a barrier in questionnaire studies in the literature (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In those efforts, three different yet comparable versions of the instrument adopted for different ages (12–13, 15–16 and 18–19) have been developed. These studies have primarily had an empirical focus and have been previously reported (Berglund & Gericke, ; Berglund, Gericke, & Chang Rundgren, ; Boeve‐de Pauw, Gericke, Olsson, & Berglund, ; Olsson & Gericke, , ; Olsson, Gericke, & Chang Rundgren, ). In the current paper, the entire development process is summarized and a complete and comprehensive description of the SCQ validation process is provided.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…We also found a significant gender-related interaction effect, indicating that gender is of relevance when performing studies in different cultural contexts. A recent study indicated that ESD-profiled schools in Sweden tend to enhance gender differences as the students get older (Olsson and Gericke 2017). The present study shows a general pattern of higher means among females than males, with one exception (Fig.…”
Section: Discussionmentioning
confidence: 99%